Evaluation of the iQ-Check®Salmonella II Assay in Select Foods: Collaborative Study, First Action 2017.06. (23rd November 2019) - Bird, Patrick; Benzinger, M Joseph; Bastin, Benjamin; Crowley, Erin; Agin, James; Goins, David; Clark, Mike; Tourniaire, Jean-Philippe; Pierre, Sophie; Lauer, Wendy; ,
Abstract: The iQ-Check Salmonella II Real-Time PCR test kit utilizes Salmonella- specific oligonucleotide probes and primers for the rapid and specific detection of Salmonella species in select food types. The alternative method was evaluated by using 375 g test portions in an unpaired study design for two matrices, milk chocolate and dry dog food. Each matrix was compared with the U.S. Food and Drug Administration Chapter 5 Salmonella reference method. Fourteen technicians from 12 laboratories, including academia and industry, located within the United States and Canada participated in the collaborative study. Three levels of contamination were evaluated for each matrix: an uninoculated control level (0 CFU/test portion), a low inoculum level (0.2–2 CFU/test portion), and a high inoculum level (2–5 CFU/test portion). The statistical analysis was conducted according to the Probability of Detection (POD) statistical model. The results obtained for the low inoculum level test portions produced a difference in the candidate presumptive and confirmatory results (dLPOD) value with a 95% confidence interval of −0.05, (−0.15, 0.06) for the milk chocolate and 0.10, (−0.01, 0.21) for the dry dog food. The dLPOD results indicate an equivalence between the candidate method and reference method for the matrices evaluated, and the method demonstrated acceptable interlaboratory reproducibility as determined in the collaborative evaluation. False positive and false negative rates were determined for each matrix and produce values of <2%. Based on the data generated, the method demonstrated acceptable interlaboratory reproducibility data and statistical analysis.